Bacterial carrier-mediated drug delivery systems: a promising strategy in cancer therapy - Yan, Sizuo; Gan, Yu; Xu, Huizhe; Piao, Haozhe (Frontiers in Bioengineering and Biotechnology, 2025)
Cancer is a major killer threatening modern human health and a leading cause of death worldwide. Due to the heterogeneity and complexity of cancer, traditional treatments have limited effectiveness. To address this problem, an increasing number of researchers and medical professionals are working to develop new ways to treat cancer. Bacteria have chemotaxis that can target and colonize tumor tissue, as well as activate anti-tumor immune responses, which makes them ideal for biomedical applications. With the rapid development of nanomedicine and synthetic biology technologies, bacteria are extensively used as carriers for drug delivery to treat tumors, which holds the promise of overcoming the limitations of conventional cancer treatment regimens. This paper summarizes examples of anti-cancer drugs delivered by bacterial carriers, and their strengths and weaknesses. Further, we emphasize the promise of bacterial carrier delivery systems in clinical translation.